2018
DOI: 10.1016/j.virusres.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Critical challenges and emerging opportunities in hepatitis C virus research in an era of potent antiviral therapy: Considerations for scientists and funding agencies

Abstract: The development and clinical implementation of direct-acting antivirals (DAAs) has revolutionized the treatment of chronic hepatitis C. Infection with any hepatitis C virus (HCV) genotype can now be eliminated in more than 95% of patients with short courses of all-oral, well-tolerated drugs, even in those with advanced liver disease and liver transplant recipients. DAAs have proven so successful that some now consider HCV amenable to eradication, and continued research on the virus of little remaining medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
128
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 121 publications
0
128
0
1
Order By: Relevance
“…Notably, although the current direct-acting antivirals treat HCV-induced disease, they do not always prevent re-infection in cured individuals. Therefore, there is an urgent need for future studies into the development of a vaccine to reduce the global burden of HCV infection (3).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, although the current direct-acting antivirals treat HCV-induced disease, they do not always prevent re-infection in cured individuals. Therefore, there is an urgent need for future studies into the development of a vaccine to reduce the global burden of HCV infection (3).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic infection dramatically increases the risk of developing liver cirrhosis and hepatocellular carcinoma (2,3). Effective direct-acting antivirals are available, but due to a high number of occult infections and the high cost of treatment, the need for a prophylactic vaccine remains high (4). Other licensed human vaccines rely mainly on inducing neutralizing antibodies (NAbs) (5), and NAbs protect against HCV infection in vivo (6,7).…”
mentioning
confidence: 99%
“…22,50 The most successful current treatment against HCV is direct acting antivirals (DAA) which have shown to eliminate HCV infection with any genotype in 95% of the cases. 23 But emerging evidence is showing the high relapse rate of DAA treatment even after successful eradication of virus. 51,52 In another study, performed in our molecular virology lab, we have reported high relapse rates of DAA against HCV patients for the first time 53 implying the need of new strategic therapies; therefore, this study is aimed to find potent antiviral genes for the eradication of different viral infection.…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…HCV infection is the cause of about half a million deaths annually and has been identified as 25 th major cause of death . The most successful current treatment against HCV is direct acting antivirals (DAA) which have shown to eliminate HCV infection with any genotype in 95% of the cases . But emerging evidence is showing the high relapse rate of DAA treatment even after successful eradication of virus .…”
Section: Introductionmentioning
confidence: 99%